2001
DOI: 10.1097/00126334-200108010-00003
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Data of a Prospective Study on Neuropsychiatric Side Effects After Initiation of Efavirenz

Abstract: Patients maintained on EFV showed a decrease in psychologic distress related to self-image, depression, and anxiety, without any effect on quality of life. Patients with a lower level of education, those who feel physically and psychologically better at baseline than in the past, and those who suffer from more distress as a result of physical complaints may be at greater risk of reporting more NPSEs after EFV initiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 18 publications
3
38
2
Order By: Relevance
“…EFV is a very potent NNRTI treatment commonly used as part of HAART; it often leads to long-lasting viral suppression (Negredo et al ., 2002). Specific neuropsychiatric toxicity, however, has been reported among patients treated with EFV, especially during the first weeks of this treatment (Blanch et al ., 2001;Lang et al ., 2001). Neuropsychiatric side effects may occur or persist for three months or longer (Lochet et al ., 2003); they may range from sleep problems to cognitive and mood disorders including sadness and suicide ideation.…”
Section: Introductionmentioning
confidence: 99%
“…EFV is a very potent NNRTI treatment commonly used as part of HAART; it often leads to long-lasting viral suppression (Negredo et al ., 2002). Specific neuropsychiatric toxicity, however, has been reported among patients treated with EFV, especially during the first weeks of this treatment (Blanch et al ., 2001;Lang et al ., 2001). Neuropsychiatric side effects may occur or persist for three months or longer (Lochet et al ., 2003); they may range from sleep problems to cognitive and mood disorders including sadness and suicide ideation.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas affective disorders related to cART were transient and self-limiting in some cases, 39,19,29 our patient suffered from persistent depression for at least five months before he stopped cART autonomously.…”
Section: Discussionmentioning
confidence: 71%
“…66 Efavirenz has long been recognised to have central nervous system (CNS) effects, which need to be taken into account when considering ART treatment in older patients. 67 Antiretroviral drugs have varying CNS penetration and it has been suggested that those with better CNS penetration will achieve superior CNS viral suppression, resulting in less neurocognitive impairment. Regimens estimated to have better CNS penetration are more effective in controlling CNS HIV RNA viral load.…”
Section: Neurological Complicationsmentioning
confidence: 99%